Analisis Kualitas Air Sebagai Pemicu Eutrofikasi di Habitat Kerang Bulu (Anadara antiquata) di Pesisir Kabupaten Pesawaran - Andy Sahalatua Gultom; Qadar Hasani; Gregorius Nugroho Susanto; Munti Sarida; Endang Linirin Widiastuti; Winarto Santosa (Journal of Tropical Marine Science, 2026)
The blood cockle (Anadara antiquata) is an economically valuable marine species that depends on suitable water quality conditions in its habitat. This study aims to analyze water quality parameters that potentially trigger eutrophication in the habitat of the blood cockle in the coastal waters of Pesawaran Regency, Lampung Province. The study was conducted at three key harvesting sites—Teluk Hurun, Teluk Cikunyinyi, and Teluk Ratai—with sampling carried out four times during September–October 2024. The measured parameters included temperature, pH, salinity, dissolved oxygen (DO), transparency, depth, nitrite, ammonia, phosphate, and total organic matter (TOM). The results showed that several chemical parameters, such as nitrite (up to 0.11 mg/L), phosphate (up to 0.63 mg/L), and TOM (up to 39.14 mg/L), exceeded marine water quality standards based on Government Regulation No. 22 of 2021. The low N/P ratio (<1) at all sites indicates a high potential for eutrophication, with Teluk Ratai identified as the most critical site. These findings highlight the importance of continuous water quality monitoring to support the sustainability of blood cockle habitats and coastal ecosystems.